2013
DOI: 10.1007/s12195-013-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nuclear Shape by Substrate Rigidity

Abstract: The nucleus is mechanically coupled to the three cytoskeletal elements in the cell via linkages maintained by the LINC complex (for Linker of Nucleoskeleton to Cyto-skeleton). It has been shown that mechanical forces from the extracellular matrix (ECM) can be transmitted through the cytoskeleton to the nuclear surface. Here we quantified nuclear shape in NIH 3T3 fibroblasts on polyacrylamide gels with a controlled degree of cross-linking. On soft substrates with a Young's modulus of 0.4 kPa, the nucleus appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 65 publications
17
127
0
Order By: Relevance
“…5). In previous studies on flat substrates, a similar trend is observed, where the nucleus height and shape index both change with increasing substrate elasticity, leading to a shorter nucleus with a rounder footprint (15,58). The NSI (Eq.…”
Section: Nsisupporting
confidence: 73%
“…5). In previous studies on flat substrates, a similar trend is observed, where the nucleus height and shape index both change with increasing substrate elasticity, leading to a shorter nucleus with a rounder footprint (15,58). The NSI (Eq.…”
Section: Nsisupporting
confidence: 73%
“…1A). Because the mechanical behavior of the nucleus has been shown to depend on tissue stiffness (Swift et al, 2013), and we have shown that the rigidity of the substratum alters nuclear shape (Lovett et al, 2013), we performed these experiments on polyacrylamide gels with sufficiently different rigidities. Remarkably, in control cells, the nuclear position closely coincided with the PMT (Fig.…”
Section: Nuclear Position Coincides With the Point Of Maximum Tensionmentioning
confidence: 99%
“…Fibronectin-coated (5 µg/ml, BD Biosciences) polyacrylamide (PAA) gels were prepared on glass-bottomed dishes (WPI, Sarasota, FL) as described previously (Lovett et al, 2013). Fluorescent microspheres of 0.5-µm diameter (Invitrogen) were suspended in the hydrogel before polymerization and used as fiduciary markers.…”
Section: Traction-force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy allows for the visualization of the NK IS en face in a single z-stack plane. Due to their morphology and adherence, NIH3T3 cells produce a monolayer of target cells and a large surface area for NK cell interaction [41][42][43]. The use of a monolayer of NIH3T3 cells is a novel experimental approach to study the NK IS.…”
mentioning
confidence: 99%